Un carteggio di Margherita Guidacci. Lettere a Tiziano Minarelli - Gepponi, Carolina (Biblioteca di Studi di Filologia Moderna, 2014)
Margherita Guidacci's correspondence with Tiziano Minarelli is filled with memories and poetic occasions, and it allows us to shed light on the genesis of her latest poetic collections (from Inno alla gioia in 1983 to Anelli del tempo in 1993), to gather new sources of inspiration and to reconstruct the emotional and cultural background accompanying the writing of the letters. This correspondence encourages reflections on the Italian literary scene, as seen from the point of view of those who, like Margherita Guidacci, contributed to it by combining poetic activity (in Italian), translation (of a a third language as well), study and teaching of the English and American literature, and cultural journalism. It testifies to an intense friendship, a common passion for literature and reading, a constant sharing of poetic texts through transcriptions and quotations, and a growing familiarity.